Inhibition of tumor formation and metastasis by a monoclonal antibody against lymphatic vessel endothelial hyaluronan receptor 1. Issue 10 (26th August 2018) - Hara, Yuta; Torii, Ryota; Ueda, Shiho; Kurimoto, Erina; Ueda, Eri; Okura, Hiroshi; Tatano, Yutaka; Yagi, Hideki; Ohno, Yoshiya; Tanaka, Toshiyuki; Masuko, Kazue; Masuko, Takashi
Abstract: Although cancer metastasis is associated with poor prognosis, the mechanisms of this event, especially via lymphatic vessels, remain unclear. Lymphatic vessel endothelial hyaluronan receptor 1 (LYVE‐1) is expressed on lymphatic vessel endothelium and is considered to be a specific marker of lymphatic vessels, but it is unknown how LYVE‐1 is involved in the growth and metastasis of cancer cells. We produced rat monoclonal antibodies (mAb) recognizing the extracellular domain of mouse LYVE‐1, and investigated the roles of LYVE‐1 in tumor formation and metastasis. The mAb 38M and 64R were selected from hybridoma clones created by cell fusion between spleen cells of rats immunized with RH7777 rat hepatoma cells expressing green fluorescent protein (GFP)‐fused mouse LYVE‐1 proteins and mouse myeloma cells. Two mAb reacted with RH7777 and HEK293F human embryonic kidney cells expressing GFP‐fused mouse LYVE‐1 proteins in a GFP expression‐dependent manner, and each recognized a distinct epitope. On immunohistology, the 38M mAb specifically stained lymphatic vessels in several mouse tissues. In the wound healing assay, the 64R mAb inhibited cell migration of HEK293F cells expressing LYVE‐1 and mouse lymphatic endothelial cells (LEC), as well as tube formation by LEC. Furthermore, this mAb inhibited primary tumor formation and metastasis to lymph nodes in metastatic MDA‐MB‐231 xenograft models. This shows that LYVE‐1 is involved in primary tumor formation and metastasis, and it may be a promising molecular target for cancer therapy. Abstract : LYVE‐1 is involved in primary tumor formation and metastasis, and may be a promising molecular target for cancer therapy with therapeutic mAb.